Working for His Majesty : Research Notes on Labor Mobilization in Late Shang China (ca. 1200-1045 B.C.), as Seen in the Oracle-Bone Inscriptions, with Particular Attention to Handicraft Industries, Agriculture, Warfare, Hunting, Construction, and the Shang's Legacies - Keightley, David N. (Book collections on Project MUSE., 2012)
"Dealing with the Shang dynasty (ca. 1200-1045 B.C.), the first to leave written records in North China, this work focuses on the artisan corps, labor mobilization, farming, warfare, hunting, building, leadership, and culture"--Provided by publisher.